A randomized equivalence trial comparing the i‐gel and laryngeal mask airway Supreme in children. Issue 2 (27th November 2012) - Jagannathan, Narasimhan; Sommers, Katherine; Sohn, Lisa E.; Sawardekar, Amod; Shah, Ravi D.; Mukherji, Isabella I; Miller, Steven; Voronov, Polina; Seraphin, Sally
Abstract: Background: The laryngeal mask airway Supreme (Supreme) is a new single‐use supraglottic device with gastric access capability now available in all sizes for children. Objectives: To compare the i‐gel with the Supreme in children for routine airway maintenance. Materials/Methods: One hundred and seventy children, aged 3 months to 11 years, 5–50 kg in weight, were randomly assigned to receive either the i‐gel or the Supreme. The primary outcome measured was airway leak pressure. Secondary outcomes included the following: ease and time for insertion, insertion success rate, fiberoptic grade of view, ease of gastric tube placement, number of airway manipulations, quality of airway during anesthetic maintenance, and complications. Results: A total of 168 patients were assessed for the outcomes. The median (IQR [range]) airway leak pressure for the i‐gel was higher than with the Supreme, 20 (18–25 [9–40]) cm H2 O vs 17 (14–22 [10–40]) cm H2 O, respectively ( P = 0.001). There were no differences in the time for device insertion, fiberoptic grade of view, quality of airway, and complications. Median (IQR[range]) time of successful insertion of a gastric tube was faster with the Supreme, 12 (9.2–14.3 [5.2–44.2]) s than with the i‐gel, 14 (11.9–19 [6.9–75]) s; P = 0.01. The number of airway manipulations during placement was higher with the i‐gel than with the laryngeal mask airway Supreme (12 vs 13 patients), P = 0.02. Conclusions: In infants and children, when a single‐use supraglottic device with gastric access capabilities is required, the i‐gel demonstrated higher airway leak pressures and can be a useful alternative to the Supreme.